A New Stochastic Model for Emergency Location Problem with Minimax Regret Model (Case Study: Mashhad) - Farshid Esmaeeli Kakhaki; Zahra Naji Azimi; Alireza Pooya; Ahmad Tavakoli (چشم‌انداز مدیریت صنعتی, 2020)
The recent increase in the number of natural disasters, earthquake in particular, underlines the need to investigate the problem of emergency location. In this study, a new hybrid approach is presented for emergency location-allocation problem which incorporates GIS, system dynamics, Coburn and Spence model, and stochastic programming. In the proposed approach, first, the candidate places are identified based on a number of indices using GIS. Since the emergency location demand is considered as an uncertain parameter depending on different scenarios of the earthquake, in the next step, a combination of system dynamics and the casualty estimation model proposed by Coburn and Spence is used to estimate the demand. Then, proposing a stochastic location-allocation model, the demand is assigned to the candidate places determined by GIS. Finally, the minimax regret model is used to identify the final locations.